ALAT SINKRONISASI OTOMATIS PLTMH DENGAN JARINGAN DISTRIBUSI PLN BERBASIS MIKROKONTROLER ATMEGA 16 - Nj. Thamrin (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
The purpose of automatic synchronization equipment is to detect the synchronization conditionals, if the conditionals have been gained, MHP electricity can be directly connected to PLN’s distribution network.The first step of this research is making censors for measuring the parameters of synchronization process. These censors are voltage censor, frequency censor, and phase angle censor. All censors are controlled by microcontroller. The measurement result of voltage and frequency are displayed on LCD. For knowing whether these censors are detected by microcontroller properly, the measurement result of censors are compared with measuring instrument. The last step is combining and testing all data in the laboratory. The electric parameters are measured for the next analysis to know these censors work properly.This synchronization tool can connect automatic 3-phase generator with PLN’s distribution network at voltage difference tolerance of ±5 %, and frequency difference of 0.2% from PLN’s distribution network. The error percentage compared to measuring tools is 2.3% for voltage and 0.091 % for frequency.Keywords                   :            Synchronization tool, microcontroller, voltage censor, zero crossing detector